2009
DOI: 10.1089/cpb.2008.0150
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use as a Predictor of Sense of Community in Older People

Abstract: The Internet opens new options for communication and may change the extent to which older people use other modes of communication. The importance of older adults' participation in cyberspace has increased as Internet use for commerce and communication has increased. The present study explores how older adults' Internet use affects their sense of community. An online survey was conducted at the University of Sydney to determine the associations between Internet use and seniors' sense of community and well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 17 publications
3
59
0
2
Order By: Relevance
“…The majority of past research on Internet and well-being has focused on children [7], adolescents [24][25][26], college students [15], older people [5,27,28], and comparisons between younger and older populations [29]. To date, few studies have looked at 'ordinary' community dwellers or relied on probability sampling techniques in their selection of participants.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of past research on Internet and well-being has focused on children [7], adolescents [24][25][26], college students [15], older people [5,27,28], and comparisons between younger and older populations [29]. To date, few studies have looked at 'ordinary' community dwellers or relied on probability sampling techniques in their selection of participants.…”
Section: Introductionmentioning
confidence: 99%
“…Attaining a sense of community can be psychologically rewarding, leading to enhanced life satisfaction and wellbeing (Sum, Mathews, Pourghasem, & Hughes, 2009). While sense of community is typically conceptualised as an offline phenomenon, individuals can also obtain this feeling in an online context (Blanchard & Markus, 2004).…”
mentioning
confidence: 99%
“…We will therefore apply concepts of Complexity Theory to our research design of interventions involving online communities of senior citizens and relate these to their subjective well-being which Wiesmann and Hannich [32] have developed as an indicator for successful ageing. These authors adopted the perspective that a sense of coherence plays a key role for psychological adaptation.…”
Section: Discussion Of Next Stepsmentioning
confidence: 99%
“…One UK digital media champion, Martha Fox, expressed concern that "over three million people aged over 65 don't see another person in a week" and believed that technology could help address this problem [8]. This is supported in a study on the use of online communities by older people, which found a positive association between a sense of belonging to an online community, sense of community and link to well-being [32]. Coughlan [11] also describes the particular health risks for the elderly in England where more than half of people over the age of 75 are living alone and about one in 10 says he or she suffers from "intense" loneliness.…”
Section: Isolation and Lonelinessmentioning
confidence: 99%